2021
DOI: 10.3390/s21030876
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Photomixer Based Slot Fed Terahertz Dielectric Resonator Antenna

Abstract: A slot fed terahertz dielectric resonator antenna driven by an optimized photomixer is proposed, and the interaction of the laser and photomixer is studied. It is demonstrated that in a continuous wave terahertz photomixing scheme, the generated THz power is proportional to the 4th power of the surface electric field of photocondutive layer. Consequently, the optical to THz conversion efficiency of the proposed photomixer has an enhancement factor of 487. This is due to the fact that the surface electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A slot-fed terahertz dielectric resonator antenna driven by an optimized photomixer is proposed in [ 1 ], and the interaction of the laser and photomixer is also studied. It is demonstrated that, in a continuous wave terahertz photomixing scheme, the generated THz power is proportional to the fourth power of the surface electric field on the photoconductive layer.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…A slot-fed terahertz dielectric resonator antenna driven by an optimized photomixer is proposed in [ 1 ], and the interaction of the laser and photomixer is also studied. It is demonstrated that, in a continuous wave terahertz photomixing scheme, the generated THz power is proportional to the fourth power of the surface electric field on the photoconductive layer.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…Also, a high isolation is achieved by designing twoport MIMO antenna with the proposed metal strip coated DR. Literature [10] proposed a dual band rectangular THz DRA based on graphene and frequency tunability achieved by varying chemical potential of graphene. An analysis of high gain graphene based circularly polarized dielectric resonator antenna (CPDRA) has been reported in [11] for THz applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, wireless links at terahertz frequencies are more susceptible to absorption and to scattering effects by atmospheric weather and suffer more serious deterioration in link performance [4,5]. In order to offset this influence, methods based on high-power antennae [6], signal repeaters [7], and adaptive signal processing [8] have been proposed and proved to be effective. Modulation identification, as an important signal processing method [9], can recognize different link modulation formats based on the weight matrix of signal features and help to decrease the response time of the entire system finally.…”
Section: Introductionmentioning
confidence: 99%